Avaliação da incorporação de cera de abelha na hidrofobização de filmes biopoliméricos e seu efeito como cobertura na conservação pós-colheita da goiaba - Oliveira, Victor Rafael Leal de (Brasil, 2017)
The development of biodegradable coatings has been potentially discussed due to the exacerbated use of petrochemical polymers, and their non-biodegradable load has been aggravating serious environmental problems. Furthermore the growing worldwide demand for health improvement has reached an interest in technological solutions capable of offering means of conservation and reduction of the metabolic activity of fruits and vegetables to preserve their numerous nutrients effectively for long periods of storage. Biopolymers, which are the polymeric base of the coating, add several positive points: they are attractive for their renewable characteristics, abundance, low cost and easy access in the semi-arid region. The coatings were synthesized by the casting method with three polymer bases: corn starch (3%), cassava starch (2%) and gelatin (5%); beeswax was added as a hydrophobic agent in the polymeric network at different concentrations relative to the dry biopolymer base (0%, 5% and 10%). The effect of the incorporation of the beeswax on the barrier properties was evaluated and the biofilm was determined with the best characteristics for coating in "Paluma" guavas, with a significant difference (p <0.05) in the addition of beeswax in cassava starch films 2%. The surface roughness and the contact angle of the systems containing beeswax indicated the hydrophobic behavior of the films. This was also confirmed by the water vapor transfer rate and solubility and led to a significant improvement in the elasticity of biofilms. "Paluma" guavas were harvested at physiological maturity and selected for the uniformity f shell color and absence of defects, were covered by the casting method with filmogenic solution of cassava starch, cassava starch with the addition of beeswax and uncoated, and then conditioned in regulated chamber at 15 ± 2 ° C and 90% -95% RH for 15 days. The physicochemical and sensorial analyzes showed that the use of the filmogenic solution of cassava starch with the addition of beeswax delayed the loss of chlorophyll and maintained a good maturation index, and consequently increased the shelf life of the guavas. The sensorial attributes: aroma, texture, acceptance and purchase intention, indicated a better acceptability of the fruits with cassava starch coating with addition of beeswax, demonstrating the commercial potential of this cover
Evaluation of the incorporation of beeswax in the hydrofobilization of biopolimeric films and its effect as a coating in the post-harvest conservation of goiaba
Keywords: Taxa de permeabilidade ao vapor d’água; Biopolímeros; Cera de abelha; Goiaba; Índice de maturação; Water vapor transfer rate; Biopolymers; Beeswax; Guava; Maturation index; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA